PENGENALAN JENIS TERIPANG DAN NILAI EKONOMIS PADA SISWA SEKOLAH MIS AL-HILAAL PULAU HATTA KECAMATAN BANDA - Maureen M. Pattinasarany; Elizabeth Miklen Palinussa; John Etry Ririhena (Universitas Mataram, 2026)
Sea cucumbers, also known as sea melons, are a type of marine animal belonging to the phylum Echinodermata. The coastal area of Hatta Island has a wide variety of aquatic resources, including various types of sea cucumbers. However, in general, significant exploitation pressure will result in a decline in population and may cause changes in the structure of the community. Introducing various types of sea cucumbers is one way to provide information and increase knowledge about economically important types of sea cucumbers. The expected objective is to provide preliminary information and increase students' knowledge about the types of sea cucumbers found in the waters so that they continue to be preserved and well cared for to ensure the sustainability of resources. The community service activity took place on September 5, 2023, for students of MIS Al-Hilaal school on Hatta Island, Banda District, Central Maluku Regency. The learning method is interactive followed by an evaluation in the form of a pre-test and post-test to assess student abilities. The results show that not all students have the same initial ability. From several questions, it is clear that 52.2% of students know what sea cucumbers are. Meanwhile, the lowest result was 12.5%. Sea cucumbers consist of several types and can be used as a food source and ingredient in the manufacture of cosmetics and medicines for various diseases. In addition, sea cucumbers have economic value, so they can be sold at a fairly high price. Then, for the final test results, around 95-100% of students were able to understand the material well. It was concluded that students gained additional knowledge and improved understanding of the types of sea cucumbers that live in the waters and their economic value, so that resources need to be preserved until harvest time.